Dari Teknologi Menuju Keberlanjutan: Peran Kesiapan Digital Dunia terhadap Indeks Tujuan Pembangunan Berkelanjutan dengan Kontrol Kualitas Lingkungan - Nicholas Chang; Luky Patricia Widianingsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of digital readiness on the achievement of Sustainable Development Goals (SDGs) by considering environmental quality as a control variable. Digital readiness is represented by the Network Readiness Index (NRI), while environmental quality is measured using the Environmental Performance Index (EPI). This study uses a quantitative approach with cross-country secondary data. Multiple linear regression analysis was used to test the relationship between variables. The results show that digital readiness has a significant positive impact on SDG achievement after being controlled for environmental quality, indicating that improving a country's digital capabilities contributes to sustainable social, economic, and environmental progress. These findings reinforce the Social-Technical Systems Theory (STST), which explains that the interaction between technical systems and socio-environmental systems is key to achieving global sustainability. In practical terms, the results of this study have policy implications that governments need to integrate the digital transformation agenda with sustainable development strategies through the strengthening of inclusive digital infrastructure. Synergy between technology investment and environmentally friendly policies is expected to accelerate the overall achievement of the 2030 SDGs.